Quality Control of Ink Bottles in Efforts to Control Defect Products in Candi Plastik Home Industry - Tri Ilma Sari; Moses Laksono Singgih (IPTEK Journal of Proceedings Series, 2020)
Quality is one of the most important things in terms of competition between companies. Products that are not of quality will be rejected. Many home industries lose competitiveness in terms of quality, it could be due to inaccurate machining. This causes a lot of product defects. A dozen years this home industry was established, but has not yet met the minimum target defect target of products set by consumers. Quite a lot of products have to be replaced and reworked. So we need a tool to control quality and detect the causes of product defects and then repair the cause. Seven tools are the seven basic tools that are able to solve the quality problems faced by production. Failure Mode Effect Analysis (FMEA) is a tool to detect the causes of production failures. The application of these two tools is expected to be able to control quality, meet the minimum specifications of consumers, detect the causes and correct the causes, increase productivity, reduce losses, and increase consumer confidence. The results of this study are seven tools and FMEA able to control product defects, the percentage of product defects produced by 22.5%, the cause of product defects is caused by 4 factors namely machinery, humans, methods, and raw materials. Whereas based on FMEA analysis, the main cause of product defects is the machine, and proposed control settings of the machine.